American juvenile justice - Zimring, Franklin E. (Oxford University Press, 2005)
This volume discusses criminology and policy analysis of adolescence. The focus is on the principles and policy of a separate and distinct system of juvenile justice. The book opens with an introduction of the creation of adolescence, presenting a justification for the category of the juvenile or a period of partial responsibility before full adulthood. Subsequent sections include empirical investigations of the nature of youth criminality and legal policy towards youth crime. At the heart of the book is an argument for a penal policy that recognizes diminished responsibility and a youth policy that emphasizes the benefits of letting the maturing process continue with minimal interruption. The book concludes with applications of the core concerns to five specific problem areas in current juvenile justice: teen pregnancy, transfer to criminal court, minority overrepresentation, juvenile gun use, and youth homicide.